On the role of supermassive black holes in quenching star formation in local central galaxies. Issue 2 (16th August 2019) - Arora, Nikhil; Fossati, Matteo; Fontanot, Fabio; Hirschmann, Michaela; Wilman, David J
ABSTRACT: We analyse the role of AGN feedback in quenching star formation for massive, central galaxies in the local Universe. In particular, we compare the prediction of two semi-analytic models (l-galaxies and sage ) featuring different schemes for AGN feedback, with the SDSS DR7 taking advantage of a novel technique for identifying central galaxies in an observational data set. This enables us to study the correlation between the model passive fractions, which is predicted to be suppressed by feedback from an AGN, and the observed passive fractions in an observationally motivated parameter space. While the passive fractions for observed central galaxies show a good correlation with stellar mass and bulge mass, passive fractions in l-galaxies correlate with the halo and black hole mass. For sage, the passive fraction correlate with the bulge mass as well. Among the two models, sage has a smaller scatter in the black hole–bulge mass (M_BH-M_Bulge) relation and a slope that agrees better with the most recent observations at z ∼ 0. Despite the more realistic prescription of radio-mode feedback in sage, there are still tensions left with the observed passive fractions and the distribution of quenched galaxies. These tensions may be due to the treatment of galaxies living in non-resolved substructures and the resulting higher merger rates that could bring cold gas which is available for star formation.